Comparative Kinetic Analysis of OXA-438 with Related OXA-48-Type Carbapenem-Hydrolyzing Class D β-Lactamases - de Belder, Denise Gisele (2020)
Novel variants of OXA-48-type enzymes with the ability to hydrolyze oxyimino-cephalosporins and carbapenems are increasingly reported. Since its first report in 2011, OXA-163 is now extensively spread throughout Argentina, and several variants like OXA-247 have emerged. Here, we characterized a new blaOXA-48-like variant, OXA-438, and we performed a comparative kinetic analysis with the local variants OXA-247 and OXA-163 and the internationally disseminated OXA-48. blaOXA-163, blaOXA-247, and blaOXA-438 were located in a 70 kb IncN2 conjugative plasmid. OXA-438 presented mutations in the vicinity of conserved KTG (214-216), with a 2-aa deletion (R220-I221) and a D224E shift (as in OXA-163) compared to OXA-48. Despite Kpn163 (OXA-163), Kpn247 (OXA-247) and Eco438 (OXA-438) were resistant to meropenem and ertapenem, and the transconjugants (TC) remained susceptible (however, the carbapenems minimum inhibitory concentrations were ≥3 times 2-fold dilutions higher than the acceptor strain). TC163 and Eco48 were resistant to oxyimino-cephalosporins, unlike TC247 and TC438. kcat/Km values for cefotaxime in OXA-163 were slightly higher than the rest of the variants that were accompanied by a lower Km for carbapenems. For OXA-163, OXA-247, and OXA-438, the addition of NaHCO3 improved kcat values for both cefotaxime and ceftazidime; carbapenems kcat/Km values were higher than for oxyimino-cephalosporins. Mutations occurring near the conserved KTG in OXA-247 and OXA-438 are probably responsible for the improved carbapenems hydrolysis and decreased inactivation of oxyimino-cephalosporins compared to OXA-163. Dichroism results suggest that deletions at the β5-β6 loop seem to impact the structural stability of OXA-48 variants. Finally, additional mechanisms are probably involved in the resistance pattern observed in the clinical isolates.